Tales from the Shadowhunter Academy - Clare, Cassandra (Margaret K. McElderry Books, 2016)
"Collects short stories chronicling Simon's journey from amnesia to Ascension, as he works to regain his lost life while attending the Shadowhunter Academy."--OCLC.